The online marketplace advantage sell more, scale faster, and create a world-class digital customer experience - Corrot, Philippe; Nussenbaum, Adrien (John Wiley & Sons, Inc., 2023)
"Traditional ecommerce business models are stagnating; online marketplaces grew at more than twice the rate of digital commerce overall in 2020. Only businesses that create online marketplaces that mirror the experience at Amazon, Alibaba, and other platforms can expect to grow significantly. The Online Marketplace Advantage breaks that monopoly on technology and gives B2B and B2C businesses the tools and know-how they need to create enterprise platforms and compete with the Amazon machine. Readers will understand their marketplace business case and operations strategy, learn the components necessary for their success, and receive a playbook for implementation within a quarter. They'll learn execution and change management best practices from Mirakl partners in the field, and receive resources for onboarding third party sellers and logistics partners. And they'll have access to Mirakl's proprietary research, including its Enterprise Marketplace Index and Enterprise Marketplace Seller Report, and case studies from global leaders."--
Includes index. - Description based on online resource; title from digital title page (viewed on April 12, 2023)
Keywords: Electronic commerce; Commerce électronique